THE SIMULATION STUDY OF GNSS SIGNAL REFLECTION IN MONITORING SEA LEVELS AND TSUNAMI - Buldan Muslim; Mokhamad Nur Cahyadi; Bambang Sunardi; Charisma Juni Kumalasari (Science of Tsunami Hazards, 2020)
A real-time Global Navigation Satellite System (GNSS) data managed by the Geospatial Information Agency (BIG) can be developed for indirect tsunami monitoring. This involves using GNSS TEC data due to the atmospheric-ionosphere coupling through tsunami- triggered infrared waves. The application of this method is, however, limited to tsunamis originating from earthquake epicenter which is far from the coast. Meanwhile, the arrival of tsunamis to the coast requires a longer time than the propagation of infrasound waves into the ionosphere. This GNSS signal reflection technique can, therefore, be used to detect tsunamis which are close to shore in order to overcome the detection weakness associated with the GNSS TEC and also routinely used to monitor sea waves. This research conducted a simulation of this technique using single-frequency code distance data to determine the sea level and the results showed its effectiveness in determining sea wave height using one differentiation. It is also possible to ignore the difference in the bias of two receivers of direct and reflected signals by sea-level assuming they are similar and have identical antennas. The use of pseudo distance from the GNSS signal code data makes it possible to estimate the height of the sea waves by simulation with a standard deviation of approximately 5.6 cm.